Active, or passive? Revisiting the role of fiscal policy in the Great Inflation - Stephanie Ettmeier; Alexander Kriwoluzky (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
We revisit the question whether U.S. fiscal policy in the pre-Volcker period was active or passive. To determine the policy stance, we estimate a DSGE model with monetary and fiscal policy interactions employing a sequential Monte Carlo algorithm (SMC) for posterior evaluation. In contrast to previous studies, we do not have to treat the different policy regimes as distinct models, which have to be estimated separately. Instead, the SMC enables us to estimate the DSGE model over its entire parameter space to determine the prevailing policy mix. Our findings attribute the leading role to the fiscal authority, while the monetary authority accommodated its actions. For active monetary/passive fiscal policy, or passive monetary/passive fiscal policy we find no evidence in the data.
Keywords: C11; C15; E63; E65; 330; Bayesian Analysis; DSGE Models; Monetary-Fiscal Policy Interactions; Monte Carlo Methods